(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Human activities, use of fertilizers and chemicals in agricultural fields are the main causes of ground water contamination. Therefore to protect and improve the natural eco system, water quality analysis is essential. The main goal of this work is to study the criteria governing the groundwater quality in the nearby wells of Peth Seer, Sopore J&K. Total 12 groundwater samples and 15 water quality parameters for each sample are considered in this study. The ground water samples of all the selected stations were collected for a physiochemical analysis. For calculating present water quality status, following 16 parameters have been considered Viz. pH, TDS, EC, Chloride concentration, Nitrate concentration, Sulphate concentration, Alkalinity, Fluoride concentration, Total hardness, Magnesium, Calcium, Sodium, Potassium, Temperature, Turbidity, Residual chlorine. The obtained results are compared with WHO (2017). The study reveals that the concentrations of all the constituents are well within the permissible limits of WHO (2017). Groundwater in the study area is suitable for drinking purpose as prescribed by WHO (2017) and irrigation purposes as prescribed by IS-11624(1986).